Trends And Innovations in the Use of Digital Science Encyclopedias - Pranggajati Ningrat; Agung Tri Prasetya; Dyah Rini Indrayanti; Novi Ratna Dewi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Digital science encyclopedias are increasingly used as alternative learning media to support students’ understanding of scientific concepts. However, evidence regarding their research trends and development challenges remains limited. This study aims to analyze research trends, implementation focus, and gaps in the use of digital encyclopedias in science education. A Systematic Literature Review combined with bibliometric analysis was conducted on 36 journal articles published between 2020 and 2025 and indexed in Google Scholar. Keyword co-occurrence and thematic relationships were analyzed using VOSviewer. The results identify three main research clusters: digital encyclopedia development and validation, student-centered implementation, and learning effectiveness with local wisdom integration. Overlay and density visualizations indicate that studies on digital encyclopedias increased between 2022 and 2023 but remain limited compared to other digital learning media. Research involving collaboration with material experts, media experts, and contextual content is still underexplored. These findings suggest that digital encyclopedias positively support science learning but require further development to enhance contextual relevance and sustainability.